Herpes simplex virus type 1 in Europe: systematic review, meta-analyses and meta-regressions. Issue 7 (16th July 2020) - Yousuf, Wajiha; Ibrahim, Hania; Harfouche, Manale; Abu Hijleh, Farah; Abu-Raddad, Laith
Abstract : Objective: To describe the epidemiology of herpes simplex virus type 1 (HSV-1) in Europe. Methods: We systematically reviewed HSV-1 related publications, conducted various meta-analyses and meta-regressions, assessed pooled mean seroprevalence, and estimated pooled mean proportions of HSV-1 viral detection in clinically diagnosed genital ulcer disease (GUD) and in genital herpes. Results: We extracted, from 142 relevant records, 179 overall (622 stratified) seroprevalence measures, 4 overall proportions of HSV-1 in GUD and 64 overall (162 stratified) proportions of HSV-1 in genital herpes. Pooled mean seroprevalence was 67.4% (95% CI 65.5% to 69.3%) with 32.5% (95% CI 29.4% to 35.7%) of children and 74.4% (95% CI 72.8% to 76.0%) of adults infected. Pooled seroprevalence increased steadily with age, being lowest in those aged <20 years (39.3%, 95% CI 35.9% to 42.7%) and highest in those aged >50 years (82.9%, 95% CI 78.8% to 86.6%). Pooled seroprevalence decreased yearly by 0.99-fold (95% CI 0.99 to 1.00). Pooled mean proportion of HSV-1 detection was 13.6% (95% CI 4.1% to 27.1%) in GUD, 34.1% (95% CI 31.7% to 36.5%) in genital herpes and 49.3% (95% CI 42.2% to 56.4%) in first episode genital herpes. Pooled proportion of HSV-1 detection in genital herpes increased yearly by 1.01-fold (95% CI 1.00 to 1.02), with higher detection in women (42.0%, 95% CI 37.4% to 46.7%) than men (24.1%, 95% CI 19.8% to 28.6%). Conclusions: HSV-1 epidemiology is transitioning away from its historical pattern of oral acquisition in childhood. Every year, seroprevalence is declining by 1% and the proportion of HSV-1 in genital herpes is increasing by 1%. As many as two-thirds of children are reaching sexual debut unexposed, and at risk of HSV-1 genital acquisition in adulthood.